Investigating the effects of individual and institutional factors on the research productivity of university academics: A comprehensive analysis - Muhammad K.; Ghani E.K.; Ilias A.; Ali M.M.; Ismail R.F.; Rohayati S.; Susanti S.; Bahtiar M.D. (Pakistan Home Economics Association, 2024)
Purpose: This study aims to examine the factors influencing the research productivity of academics in Malaysian universities. Specifically, this study examines whether individual and institutional factors can influence academics research productivity. Design/Methodology/Approach: This study utilized a questionnaire survey as the research instrument, which was distributed to university academics in Malaysia. Findings: This study demonstrates that institutional factors significantly influence the research productivity of university academics. The findings of this study suggest that institutional factors should be taken into consideration when developing strategies to increase the research productivity of university academics. However, the study did not find significant evidence to support the influence of individual factors on research productivity. Conclusion: The results of this study constitute a timely addition to the body of knowledge on academic research output, which educational leaders of Malaysian public institutions can utilize. Research Limitations/Implications: The outcomes of this study are expected to assist universities in developing strategies to assist and support academics in improving their research productivity. Practical Implications: The findings imply that universities could raise awareness of the value of research among academics and support them through publication funding or training programs. Contribution to Literature: This study contributes to the existing literature by providing evidence on the effect of individual and institutional factors on the academics research productivity. 2023 by the authors. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).